2014
DOI: 10.1016/j.enpol.2013.10.023
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating life cycle external cost in optimization of the electricity generation mix

Abstract: The present work aims to examine the strategic decision of future electricity generation mix considering, together with all other factors, the effect of the external cost associated with the available power generation technology options, not only during their operation but also during their whole life-cycle. The analysis has been performed by integrating the Life Cycle Assessment concept into a linear programming model for the yearly decisions on which option should be used to minimise the electricity generati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(24 citation statements)
references
References 68 publications
(66 reference statements)
1
19
0
1
Order By: Relevance
“…Most programs such as WASP IV, EMCAS, UPLAN, and AURORAxmp use such functions [25,26]. On the other hand, recent studies have considered not only such nominal costs of power generation but also the external costs or policy objectives-such as environmental effects [6][7][8][9], energy security [2,10,11], related risk [3,[12][13][14], future uncertainty [15], and other energy policy goals [16][17][18]-as additional constraints. Most of these studies utilize a multi-objective optimization model or portfolio theory.…”
Section: Literature Review: Optimal Electricity Generation MIXmentioning
confidence: 99%
See 1 more Smart Citation
“…Most programs such as WASP IV, EMCAS, UPLAN, and AURORAxmp use such functions [25,26]. On the other hand, recent studies have considered not only such nominal costs of power generation but also the external costs or policy objectives-such as environmental effects [6][7][8][9], energy security [2,10,11], related risk [3,[12][13][14], future uncertainty [15], and other energy policy goals [16][17][18]-as additional constraints. Most of these studies utilize a multi-objective optimization model or portfolio theory.…”
Section: Literature Review: Optimal Electricity Generation MIXmentioning
confidence: 99%
“…Examples of such external costs include human health problems, environmental degradation, energy security, dangers of a major accident with a power plant, etc. In recent years, recognition and responsibility for such external costs of electricity and their internalization have become an important policy issue [5], and thus, recent studies have proposed an electricity mix developed under various constraints [2,3,[6][7][8][9][10][11][12][13][14][15][16][17][18]. This context might explain the global phenomenon in which the proportion of renewable energy is increasing even though it has a lower economic feasibility than conventional energy sources.…”
Section: Introductionmentioning
confidence: 99%
“…The current work goes beyond previous research by Rentizelas and Georgakellos [10] and others in several respects. First, a MILP multiperiod model up to 2060 has been developed that can optimise electricity supply on both life cycle costs and environmental impacts, allowing for their trade-offs to be explored.…”
Section: Introductionmentioning
confidence: 92%
“…A recent work by Rentizelas and Georgakellos [10], while taking a life cycle approach, did not use MILP but linear programming, which was applied to plan generation capacity in Greece up to 2050. Furthermore, the authors considered environmental impacts related only to air pollution, assigning them a monetary value to estimate the externalities from electricity generation.…”
Section: Introductionmentioning
confidence: 99%
“…Rentizelas incorporated life cycle external costs in optimization of the electricity generation mix. The results indicated that renewable energy, especially wind and biomass, should be the new generating capacity [17]. Since biomass power generation project is still on the primary stage, external costs of biomass co-fired with coal power generation are estimated in many studies [18][19][20][21].…”
Section: Literature Reviewmentioning
confidence: 99%